Odpowiedzi

  • Użytkownik Zadane
2010-02-24T17:33:02+01:00
A) (5a+4-11b)+(8b-7a)= 5a+4-1-11b+8b-7a=-2a-3b+3

b) (x-3y)+(-2x-8y)=x-3y-2x-8y=-x-11y

c) (4m+3n)-(2m-7n+3)=4m+3n-2m+7n-3=2m+10n-3

d) (a-2b)-(4a+5b)=a-2b-4a-b= -3a-3b

mam nadzieje ze pomoglam i licze na naj;)
1 5 1
2010-02-24T17:43:11+01:00
A)=5a+4-11b+8b-7a=-2a-3b+4
b)=x-3y-2x-8y=-x-5y
c)=4m+3n-2m+7n-3=2m+10n-3
d)=a-2b-4a-5b=-3a-7b
1 5 1
2010-02-24T17:48:25+01:00
A) 117ab-35a(kwadrat)-32b-28a-88b(kwadrat)
b)2x(kwadrat)+14xy+8y(kwadrat)
c)2m+10n-3
d)-3a-7b
1 5 1